An Empirical Approach to Understanding Privacy Concerns - Luc Wathieu; Allan Friedman (European School of Management and Technology (ESMT), 2009)
This paper shows that privacy concerns in commercial contexts are not solely driven by a desire to control the transmission of personal information or to avoid intrusive direct marketing campaigns. When they express privacy concerns, consumers anticipate indirect economic consequences of data use, such as price discrimination. Our general hypothesis is that consumers are capable of expressing differentiated levels of concerns in the presence of changes that suggest indirect consequences of information transmission. We suggest that there is a homo economicus behind privacy concerns, not simply a primal fear. This hypothesis is tested in a large-scale experiment evoking the context of affinitybased direct marketing of insurances, which relies on data transmitted by alumni associations. Because opt-in and opt-out choices offered by firms to consumers usually capture non-situational preferences about data transmission, their ability to enact privacy concerns is questioned by our findings.
urn:nbn:de:101:1-201106143564
Keywords: D8; M38; 650; privacy; opt-in/opt-out; insurance; Datenschutz; Konsumentenverhalten; Informationsverbreitung; Test